'Bansai, bansai, it's better to write then die': Patti Smith as icon of the contemporary writing memoir. Issue 1 (2nd January 2022) - Masschelein, Anneleen
ABSTRACT: Patti Smith's failure to perform her cover of Dylan's 'A Hard Rain's A-Gonna Fall' flawlessly at the Nobel ceremony in 2016 provides an unexpected insight into the complex dynamics that shape contemporary literary culture. Both the consistency of Smith's poetics and the importance of failure in her work reinforce an aura of authenticity and individuality that has given a new lease on her status as 'icon'. Zooming in on the practice of 'covering' that runs through Smith's work, I want to uncover a new literary voice that gradually emerges alongside Smith's longstanding devotion to high literature and her 'masculine' artist ethos, an authorial position that is both untimely and very much in tune with a dominant trends of contemporary literature, i.e. the writing memoir. In her writing memoir M Train (2015), Smith creates a portrait of a female artist later in life, living alone, for whom writing and reading is a life-style in the fullest sense of the word. Trying to appropriate the posture of the Great Author, Smith continually 'fails' in her desire to be one. Yet in assuming her failure she cannily claims and queers her position as a contemporary American Author.